2009
DOI: 10.1007/s11242-009-9426-x
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on the Influence of Sub-Core Scale Heterogeneities on CO2 Distribution in Reservoir Rocks

Abstract: This article presents the results of CO 2 /brine two-phase flow experiments in rocks at reservoir conditions. X-ray CT scanning is used to determine CO 2 saturation at a fine scale with a resolution of a few pore volumes and provide 3D porosity and saturation maps that can be use to correlate CO 2 saturations and rock properties. The study highlights the strong influence of sub-core scale heterogeneities on the spatial distribution of CO 2 at steady state and provides useful relative permeability data on a sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
204
1
2

Year Published

2013
2013
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 324 publications
(225 citation statements)
references
References 14 publications
18
204
1
2
Order By: Relevance
“…The viscosity ratio is defined as the ratio of the advancing non-wetting fluid viscosity to the defending wetting fluid viscosity (η w ), i.e., M = η n /η w . In addition, recent laboratory studies [41][42][43][44] have shown the strong influence of subcore scale heterogeneities on steady-state migration patterns, spatial distributions, and fluid saturations. To gain a better understanding of pore-scale two-phase displacement mechanisms, a series of numerical simulations are conducted to study the effect of Ca and M on displacement stability and fluid saturation in a homogeneous and a heterogeneous pore networks, and the obtained results are compared to indicate the effect of media heterogeneity.…”
Section: Resultsmentioning
confidence: 99%
“…The viscosity ratio is defined as the ratio of the advancing non-wetting fluid viscosity to the defending wetting fluid viscosity (η w ), i.e., M = η n /η w . In addition, recent laboratory studies [41][42][43][44] have shown the strong influence of subcore scale heterogeneities on steady-state migration patterns, spatial distributions, and fluid saturations. To gain a better understanding of pore-scale two-phase displacement mechanisms, a series of numerical simulations are conducted to study the effect of Ca and M on displacement stability and fluid saturation in a homogeneous and a heterogeneous pore networks, and the obtained results are compared to indicate the effect of media heterogeneity.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, previous studies in which supercritical CO 2 was used indicate a thicker permeation front region with 3 to 13.4 PV injected before CO 2 saturation reached a steady distribution (14,15) . The influence of the sub-core scale heterogeneity was discussed by Perrin et al (14) and Shi et al (15) , and recent studies noted that permeability discontinuities cause saturation discontinuities (18,19) . In this study, a thin laminar structure in a large-diameter sandstone sample can be observed by employing microfocus X-ray CT.…”
Section: Effect Of Thin Laminar Heterogeneity For Co 2 Permeation Promentioning
confidence: 74%
“…The porosity and CO 2 saturation of the sandstone were measured by X-ray CT and mapped from several images or by varying the X-ray energy (12)(13)(14) . In this study, six images at constant X-ray energy were obtained for each of: the dry and water-saturated sample holder without the sandstone; the water and CO 2 saturated sandstone (the core was filled …”
Section: Measurement Of Porosity and Co 2 Saturationmentioning
confidence: 99%
See 1 more Smart Citation
“…an uncertainty that is similar in strength to 120 spatial variations in the porosity of many reservoir rocks at the same scale [32,121 33, [17][18][19]. As explained in a previous publication [13], this uncertainty can be 122 assessed by subtracting two scans that have been taken at the same position and 123 it can be significantly reduced by proper combination of sufficient repeated mea-124 surements and image coarsening (see Section 3.2).…”
mentioning
confidence: 99%